Development of Interactive E-modules Using Problem Based Learning Model the Independent Curriculum to Entrance High School Student Critical Thingking Skils - Apriani, Yelsi; Medriati, Rosane; Setiawan, Iwan (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2025)
This research focuses on evaluating the feasibility, student responses, and the enhancement of critical thinking skills among high school learners through the use of a Problem-Based Learning (PBL) interactive e-module centered on heat and thermodynamics. Utilizing the Research and Development (R&D) approach through the ADDIE framework, which comprises five distinct phases: analysis, design, development, implementation, and evaluation, the study employed various instruments like observations, interviews, questionnaires, and assessments of critical thinking skills. The findings indicated that the interactive e-module is highly feasible, achieving a score of 87.96%. Student feedback regarding the e-module was also overwhelmingly positive at 82.24%. Furthermore, the assessment of critical thinking enhancements indicated a significant improvement, with an N-Gain of 0.71 categorized as high when comparing pretest and posttes scores. In summary, the interactive e-module developed under the PBL framework is not only appropriate for testing but also significantly boosts students' critical thinking abilities.